2011
DOI: 10.4067/s0034-98872011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas climatéricos y calidad de vida de usuarias de consultorios de atención primaria de salud, Santiago

Abstract: (Rev Med Chile 2011; 139: 618-624).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…In a study by Bahriand colleagues (2013), there was no significant relationship between the severity of menopausal symptoms with anxiety and depression (23), which is also inconsistent with the results of the present study, possibly due to the difference in the measurement scale of menopausal symptoms. On the other hand, a study by Lopez et al (2011) showed a significant relationship between lifestyle dimensions, physical activity, interpersonal relationships and spiritual growth with the number and severity of hot flashes and the number and severity of nightly sweating (24), which is partly in line with the results of our study. Furthermore, an earlier work by Ivarsson et al (1998) found that by increasing physical activity, the severity of hot flashes reduced (25).…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Bahriand colleagues (2013), there was no significant relationship between the severity of menopausal symptoms with anxiety and depression (23), which is also inconsistent with the results of the present study, possibly due to the difference in the measurement scale of menopausal symptoms. On the other hand, a study by Lopez et al (2011) showed a significant relationship between lifestyle dimensions, physical activity, interpersonal relationships and spiritual growth with the number and severity of hot flashes and the number and severity of nightly sweating (24), which is partly in line with the results of our study. Furthermore, an earlier work by Ivarsson et al (1998) found that by increasing physical activity, the severity of hot flashes reduced (25).…”
Section: Discussionsupporting
confidence: 93%
“…The same authors [21][22][23][24] indicate that smoking was present in women with the highest complaints about hot flushes and low life quality. Although strongly related with estrogen deficiency, the hot flushes could be enhanced by nicotine side effects.…”
Section: Menopausementioning
confidence: 93%
“…34 Currently, due to restriction on indication of hormone replace therapies; it has been tried alternative strategies in order to relieve the climacteric symptoms, including the yoga practice, which has positive results with insomnia problems and is improving the life quality of these patients; acupuncture for anxiety relieve; and physical activity, antidepressant and phytoestrogens for reduction of hot flushes. 35 Eight studies [10][11][12][13][14][20][21][22] reinforced the negative impact of those symptoms that will lead to a life quality decrease of climacteric women, with chances to stand through their lives. The authors also remember that factors as cultural circle, civil status and professional activity could also influence the climacteric syndrome, which means that the climacteric condition it is individual, varying for each woman.…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…Uma gama de estudos com diferentes desenhos metodológicos tem sido realizada enfocando a relação da QV com o climatério em populações e culturas distintas. Em sua maioria, esses estudos apontam uma relação inversa entre os diversos sinais e sintomas da síndrome climatérica e a QV [4][5][6] . A despeito disso, ainda surgem indagações acerca do real impacto do climatério sobre a QV das mulheres, especialmente quanto à interferência direta ou indireta de fatores psicossociais e culturais relacionados ao processo de envelhecimento 1,4,7 .…”
Section: Introductionunclassified